Copulation behaviour of Glossina pallidipes (Diptera: Muscidae) outside and inside the female, with a discussion of genitalic evolution - Briceño Lobo, Daniel (2007)
artículo (arbitrado)--Universidad de Costa Rica. Escuela de Biología, 2007